If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 5(3 + -1m) = 3 + -4m 3m + (3 * 5 + -1m * 5) = 3 + -4m 3m + (15 + -5m) = 3 + -4m Reorder the terms: 15 + 3m + -5m = 3 + -4m Combine like terms: 3m + -5m = -2m 15 + -2m = 3 + -4m Solving 15 + -2m = 3 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. 15 + -2m + 4m = 3 + -4m + 4m Combine like terms: -2m + 4m = 2m 15 + 2m = 3 + -4m + 4m Combine like terms: -4m + 4m = 0 15 + 2m = 3 + 0 15 + 2m = 3 Add '-15' to each side of the equation. 15 + -15 + 2m = 3 + -15 Combine like terms: 15 + -15 = 0 0 + 2m = 3 + -15 2m = 3 + -15 Combine like terms: 3 + -15 = -12 2m = -12 Divide each side by '2'. m = -6 Simplifying m = -6
| 9t^2-8t+(16/9) | | 10x^2-4=3x | | y=2x-1/2 | | 10x^2=15-7x | | 1/5=y+2/5 | | (3x+14)/2=4 | | 5x+2=1(x+4) | | x/4=y+2 | | 35*7k/4 | | -5+10=16x-4-15x | | 12x+2=1(x+4) | | 8.6+4.1(x)=x+77.9 | | 4y-1=2+1 | | .05*.05*.05*.05= | | -5(4t-2)+7t=8t-6 | | 8.6+4.1x=x+77.9 | | 12x-2=1(x+4) | | -8=(x+68)/-9 | | 8a-3(a-4)=3 | | 12x-2=1(x-3) | | 2x+7=3x-2 | | (3x+7)/4=-2 | | 9x+7=9(x+1) | | 11x-2=1(x-3) | | 21+3f=9-3f | | (x/6)-2=(x/6) | | (2x+1)(-6x+5)=0 | | 0.002h-4=0.02+4h-8 | | 3x+7/4=-2 | | 2377960+26x=-1825 | | 15x+1=yforc | | 3+(x-3)=x+1 |